Pengaturan Dan Konsep Pemaafan Hakim (Rechterlijk Pardon Atau Judicial Pardon) Dalam Perspektif Kuhp Nasional: Analisis Terhadap Asas Keadilan, Kepastian Hukum, Dan Kemanfaatan - Derry Angling Kesuma (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2026)
This study is based on the issue of the lack of detailed provisions and mechanisms for the implementation of judicial pardons (rechterlijk pardon or judicial pardon) in the National Criminal Code, particularly in efforts to achieve a balance between justice, legal certainty, and public interest. In the context of criminal law reform, judicial pardons can be viewed as one of the instruments reflecting a shift in the orientation of Indonesian criminal law toward a more proportional and balanced approach. The existence of this mechanism provides judges with the flexibility to consider aspects of justice and public interest when rendering a verdict, rather than focusing solely on the imposition of criminal sanctions. However, the application of judicial pardons must be supported by clear guidelines to prevent differing interpretations or inconsistencies in judicial practice. Therefore, it is necessary to develop more concrete implementation guidelines, both through the establishment of consistent case law and through institutional instruments such as Supreme Court Regulations (PERMA) and Supreme Court Circular Letters (SEMA). Such clarity is essential to provide guidance to judges in applying judicial pardons while maintaining the consistency of rulings and public trust in the judicial system. Ultimately, a more focused regulation and application of judicial pardons are expected to support the goal of national criminal law reform in building a criminal justice system that is fair, humane, and capable of responding to societal dynamics and needs.